Analisis Peran Pembelajaran IPS dalam Upaya Mengatasi Ketimpangan Sosial Masyarakat di Indonesia - Mhd.Ardiansah Hrp; Fauzan Habibi; Jumintan Jumintan; Siti Sabilah; Yuli Ramadhani; Aliyah Putri; Siti Khodijah; Nurhayati Siregar (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Social inequality is an injustice in status and position felt by society. This article discusses a Literature Study Regarding the Role of Social Sciences (IPS) in Addressing Social Inequality in Indonesian Society. The purpose of this article was written to determine how the problem of inequality occurs in society and what solutions to overcome social inequality in Indonesia. The research method used is a library research method with a descriptive approach in explaining the Role of Social Sciences (IPS) in Addressing Social Inequality in Indonesia. The role of social sciences(IPS) is very important in fostering social awareness to overcome social inequality that occurs in society. The role of IPS not only emphasizes the discussion on understanding the material, but also examines various relevant social issues in the community. Therefore, social studies education must be designed in such a way that it can address relevant social issues and invite social levels in society to actively participate in a critical and reflective learning process in realizing positive social change in the community.